Incestuous Sexual Violence Against Girls and Family Dysfunction in Coastal Indonesia: Causes, Consequences, and Legal Handling Effectiveness - Nurcahaya, Nurcahaya; Karimuddin, Karimuddin (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
This study examines cases of incestuous sexual violence against girls perpetrated by biological fathers within the family structure. The primary focus is to identify the underlying causes and consequences of incest, as well as to analyze the effectiveness of the legal responses. Employing a case study approach and utilizing Focus Group Discussions (FGDs), data were collected through engagements involving the Office for the Empowerment of Women and Child Protection (P3A), the National Commission on Violence Against Women (Komnas Perempuan), and various women’s and child protection organizations. The findings reveal that incestuous sexual violence against girls is driven by a combination of structural and cultural factors, particularly poverty, lack of privacy within the household, communal living arrangements, and dysfunctional family relationships. These conditions create an environment of heightened vulnerability for girls. In practice, legal handling of incest cases has not received adequate attention from the government. In contrast, civil society organizations focused on women and child protection have demonstrated a more proactive response, although their efforts are often hindered by the absence of clear legal regulations and insufficient institutional coordination. The presence of the state in ensuring legal protection for victims is thus critically important. This study underscores the need for strengthening a victim-oriented legal system, as well as the importance of preventive strategies through Islamic family law education. Such education is expected to foster collective awareness regarding the protection of girls within the family structure, particularly in coastal communities across Indonesia.